2011
DOI: 10.1111/j.1365-2966.2011.19302.x
|View full text |Cite
|
Sign up to set email alerts
|

The origin of RX J1856.5−3754 and RX J0720.4−3125 - updated using new parallax measurements

Abstract: RX J1856.5−3754 and RX J0720.4−3125 are the only young isolated radio‐quiet neutron stars (NSs) for which trigonometric parallaxes were measured. Due to detection of their thermal emission in X‐rays, they are important to study NS cooling and to probe theoretical cooling models. Hence, a precise determination of their age is essential. Recently, new parallax measurements of RX J1856.5−3754 and RX J0720.4−3125 were obtained. Considering that NSs may originate from binary systems that got disrupted due to an asy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 99 publications
5
48
0
1
Order By: Relevance
“…Neutron star parameters: heliocentric radial velocity v r , distance d or parallax π, proper motion µ * α , µ δ , peculiar space velocity v sp ; Predicted supernova position: distance of the supernova to Earth at the time of the supernova (d ,SN ) and as seen today (d ,today ), Galactic coordinates (Galactic longitude l, Galactic latitude b, J2000.0) as seen from the Earth today; Predicted time of the supernova in the past τ . For the derivation of the parameters we refer the reader to the work of Tetzlaff et al 2010 previously by Hoogerwerf et al (2001), Bobylev & Bajkova (2009), and by ourselves (Tetzlaff et al 2014(Tetzlaff et al , 2011a(Tetzlaff et al , 2009(Tetzlaff et al , 2010(Tetzlaff et al , 2012, to account for all errors on the observables. Among all young nearby neutron stars 5 in the ATNF pulsar database 6 with available distance and proper motion (105 neutron stars in total, see Tetzlaff 2013), we find two candidates for a common origin with HIP 9470: PSR J0358+5413 and PSR J0152−1637.…”
Section: Past Trajectoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutron star parameters: heliocentric radial velocity v r , distance d or parallax π, proper motion µ * α , µ δ , peculiar space velocity v sp ; Predicted supernova position: distance of the supernova to Earth at the time of the supernova (d ,SN ) and as seen today (d ,today ), Galactic coordinates (Galactic longitude l, Galactic latitude b, J2000.0) as seen from the Earth today; Predicted time of the supernova in the past τ . For the derivation of the parameters we refer the reader to the work of Tetzlaff et al 2010 previously by Hoogerwerf et al (2001), Bobylev & Bajkova (2009), and by ourselves (Tetzlaff et al 2014(Tetzlaff et al , 2011a(Tetzlaff et al , 2009(Tetzlaff et al , 2010(Tetzlaff et al , 2012, to account for all errors on the observables. Among all young nearby neutron stars 5 in the ATNF pulsar database 6 with available distance and proper motion (105 neutron stars in total, see Tetzlaff 2013), we find two candidates for a common origin with HIP 9470: PSR J0358+5413 and PSR J0152−1637.…”
Section: Past Trajectoriesmentioning
confidence: 99%
“…We note, however, that only about 35 per cent of former runaway star/neutron star pairs can be recovered due to the large uncertainties on the observables (Tetzlaff 2013). Owing to the unknown radial velocity of neutron stars, their flight paths can only be traced back up to a maximum of a few Myr (we use 5 Myr, e. g. Tetzlaff 2013;Tetzlaff et al 2011aTetzlaff et al , 2010). This also sets a limit on the maximum age of the runaway star.…”
Section: Past Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tetzlaff et al (2011), the direction of motion was determined to be 62 ± 9 • , by tracing back the motion of RX J0720.4−3125 to its possible birth association Trumpler−10. The direction of motion determined kinematically is thus roughly consistent with almost alignment of spin and orbit.…”
Section: Fittedmentioning
confidence: 99%
“…Empirical evidence for this comes from our X-ray timing efforts (Kaplan & van Kerkwijk 2005a, 2005b, 2009a, 2009bvan Kerkwijk & Kaplan 2008), which showed that the current field strengths of the INSs are remarkably similar, in the range (1.0-3.5) × 10 13 G, and that their characteristic ages of several Myr are substantially in excess of true ages of ∼0.5 Myr inferred from cooling and kinematics (Walter 2001;Motch et al 2005;Kaplan et al 2007;van Kerkwijk & Kaplan 2008;Motch et al 2009;Tetzlaff et al 2010Tetzlaff et al , 2011. The long periods and characteristic ages follow naturally if the INSs initially had much stronger fields and thus faster spin-down, and the similar current field strengths can be understood if fields stop decaying at a common value.…”
Section: Introductionmentioning
confidence: 99%